2018
DOI: 10.1051/e3sconf/20183102007
|View full text |Cite
|
Sign up to set email alerts
|

Biogas Production from Rice Husk Waste by using Solid State Anaerobic Digestion (SSAD) Method

Abstract: Abstract. An effort to obtain alternative energy is still interesting subject to be studied, especially production of biogas from agriculture waste. This paper was an overview of the latest development of biogas researches from rice husk waste by Solid State Anaerobic Digestion (SSAD). The main obstacle of biogas production from rice husk waste was the lignin content which is very difficult degraded by microbes. Various pretreatments have been conducted, either physically, chemically as well as biologically. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 17 publications
1
1
0
Order By: Relevance
“…It was observed that the maximum biogas production occurred on day 15 at a pH value of 6.96. This is in agreement with the result by Hashfi and Hadiyanto [32] that the optimal pH condition for methanogenic bacteria varied between 6.8 and 7.6.…”
Section: Influence Of Ph On Biogas Production From Each Substratesupporting
confidence: 93%
“…It was observed that the maximum biogas production occurred on day 15 at a pH value of 6.96. This is in agreement with the result by Hashfi and Hadiyanto [32] that the optimal pH condition for methanogenic bacteria varied between 6.8 and 7.6.…”
Section: Influence Of Ph On Biogas Production From Each Substratesupporting
confidence: 93%
“…Mussoline et al [70] mentioned that optimum digestion conditions of pH (6.5-8.0), temperature (35-40 • C), and nutrients (C:N ratio of 25-35) could produce methane yields of 92-280 l/kg of volatile solids. Matin et al [71] investigated the development of biogas production from rice husk by solid-state anaerobic digestion (SSAD) and found that lignin content was very difficult to degrade using microbes. They also found that a better biogas yield was produced by using the SSAD method compared with liquid anaerobic digestion (LAD).…”
Section: Anaerobic Digestionmentioning
confidence: 99%